Paraoxon Attenuates Vascular Smooth Muscle Contraction through Inhibiting Ca(2+) Influx in the Rabbit Thoracic Aorta - Zhou, Shouhong (Hindawi Publishing Corporation, 2010)
We investigated the effect of paraoxon on vascular contractility using organ baths in thoracic aortic rings of rabbits and examined the effect of paraoxon on calcium homeostasis using a whole-cell patch-clamp technique in isolated aortic smooth muscle cells of rabbits. The findings show that administration of paraoxon (30 μM) attenuated thoracic aorta contraction induced by phenylephrine (1 μM) and/or a high K(+) environment (80 mM) in both the presence and absence of thoracic aortic endothelium. This inhibitory effect of paraoxon on vasoconstrictor-induced contraction was abolished in the absence of extracellular Ca(2+), or in the presence of the Ca(2+) channel inhibitor, verapamil. But atropine had little effect on the inhibitory effect of paraoxon on phenylephrine-induced contraction. Paraoxon also attenuated vascular smooth muscle contraction induced by the cumulative addition of CaCl(2) and attenuated an increase of intracellular Ca(2+) concentration induced by K(+) in vascular smooth muscle cells. Moreover, paraoxon (30 μM) inhibited significantly L-type calcium current in isolated aortic smooth muscle cells of rabbits. In conclusion, our results demonstrate that paraoxon attenuates vasoconstrictor-induced contraction through inhibiting Ca(2+) influx in the rabbits thoracic aorta.